The Role of Green Productx and Environmental Knowledge in Supporting a Healthy Lifestyle of Gen. Z - Yunita, Irma; Handayani, E. Egriana; Rusdianah, Iim (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
Consumer behavior, fundamental in the Interest of buying green products, should be based on the understanding of a healthy lifestyle, yet deficit on practice. This quantitative study investigates the elusive influence of green products, environmental knowledge, and healthy lifestyle on purchasing interests and to what extent the implications of physical activity moderate it. This research collected responses from 350 Gen. Z for the measurement analysis in the PLS-SEM. The findings indicate that green products, health awareness, environmental knowledge, and a healthy lifestyle are related to Interest in buying green products. The moderating role of physical activity only supports environmental knowledge. Thus, a healthy lifestyle implies the critical need for continuous socialization of green products and, consequently, public health.